2016
DOI: 10.1016/j.cyto.2016.06.017
|View full text |Cite
|
Sign up to set email alerts
|

JAK-STAT signaling in cancer: From cytokines to non-coding genome

Abstract: In the past decades, studies of the Janus kinases (JAKs) and signal transducers and activators of transcription (STATs) signaling have uncovered highly conserved programs linking cytokine signaling to the regulation of essential cellular mechanisms such as proliferation, invasion, survival, inflammation and immunity. Inhibitors of the JAK/STAT pathway are used for treatment of autoimmune diseases, such as rheumatoid arthritis or psoriasis. Aberrant JAK/STAT signaling has been identified to contribute to cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
137
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(144 citation statements)
references
References 196 publications
(192 reference statements)
0
137
0
Order By: Relevance
“…Similarly, loss of SOCS1, which is a critical mediator of T cell homeostasis, has been associated with the upregulation of known IRG PD-L1 and T cell inactivation resulting from uncontrolled IFN signaling [130]. Multiple miRNAs have also been shown to modulate SOCS expression [132]. In breast cancer, the suppression of SOCS1 by miR-155, which is required for effector T cell responses, resulted in enhanced JAK2-STAT3 signaling by more than three-fold, and it was linked to inflammation-driven tumor progression [133].…”
Section: Stat Signaling: Interactions and Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, loss of SOCS1, which is a critical mediator of T cell homeostasis, has been associated with the upregulation of known IRG PD-L1 and T cell inactivation resulting from uncontrolled IFN signaling [130]. Multiple miRNAs have also been shown to modulate SOCS expression [132]. In breast cancer, the suppression of SOCS1 by miR-155, which is required for effector T cell responses, resulted in enhanced JAK2-STAT3 signaling by more than three-fold, and it was linked to inflammation-driven tumor progression [133].…”
Section: Stat Signaling: Interactions and Inhibitionmentioning
confidence: 99%
“…This includes IL-1β, implicated in driving tumorigenesis and promoting TAM recruitment to the TME, thus highlighting the contextual and opposing functions of PIAS family members. In addition to SOCS proteins, studies have shown that the small and long non-coding RNA also regulates PIAS members [132]. Interaction between miRNA-18a and PIAS3 has been implicated in the development of gastric cancer through the overactivation of STAT3 when PIAS3 is silenced [132].…”
Section: Stat Signaling: Interactions and Inhibitionmentioning
confidence: 99%
“…Activating mutations of JAK1 and STAT3 genes were found in 20% of ALK − ALCLs, 38% of which displayed double lesions [12]. As the JAK/STAT pathway has a critical role in hematopoietic development, it is not surprising that it plays, when deregulated, an important oncogenic role in lymphoproliferative malignancies [13]. Many cancers and hematologic malignancies have been associated with the constitutive activation of the STAT family of proteins, which depends on JAK-mediated tyrosine phosphorylation for transcriptional activation [14].…”
mentioning
confidence: 99%
“…This pathway's activity is likewise required for the same phenomena in Drosophila [20][21][22][23][24][25][26], among others [27][28][29][30][31][32], though the pathway involves only one transmembrane receptor [Domeless (Dome)], one JAK [Hopscotch (Hop)], one STAT (Stat92E), and three activating ligands (Upd1-3). Disruption of this signaling cascade has been implicated in oncogenesis and tumor metastasis because of its contributions to these processes (reviewed in [33,34]). Disruption of this signaling cascade has been implicated in oncogenesis and tumor metastasis because of its contributions to these processes (reviewed in [33,34]).…”
mentioning
confidence: 99%
“…The role of JAK/STAT signaling in these events is governed by its more general involvement with cell migration, differentiation, and proliferation. Disruption of this signaling cascade has been implicated in oncogenesis and tumor metastasis because of its contributions to these processes (reviewed in [33,34]). Unfortunately, the intricacy of mammalian JAK/STAT signaling creates a barrier to elucidating key molecular targets for the development of novel cancer remediation strategies.…”
mentioning
confidence: 99%